Drug and Protein Encapsulation by Emulsification: Technology Enhancement Using Foam Formulations - Tan, M.; Danquah, Michael (WILEY-V C H VERLAG GMBH, 2012)
Significant progress has been made in developing formulations for protein and drug encapsulation and delivery. The most frequently used method is the emulsion/solvent removal technology, where microencapsulation of proteins in polymeric matrices can be easily achieved with a simple stirrer setup. However, it remains a challenge to produce protein-encapsulated formulations with high encapsulation efficiencies. The emulsion/solvent removal technique and the relevant formulation and process parameters that govern the protein encapsulation processes are reviewed. A new encapsulation method of using foam as a delivery medium during the preparation of protein-loaded microparticles is proposed. The foam characteristics of direct relevance to protein encapsulation are discussed. The unique properties of foam could enhance intermolecular interactions and access to internal pore surfaces, thus making them superior compared to traditional methods employing aqueous liquid phases during protein encapsulation. The emulsion/solvent removal technique for production of protein-loaded microparticles including the relevant formulation and process parameters governing protein encapsulation are reviewed. A new encapsulation method using foam as a delivery medium for preparation of protein-loaded microparticles is proposed. The foam characteristics of direct relevance to protein encapsulation are discussed.